Kepemimpinan Transformasional Dan Pemberdayaan Serta Pengaruhnya Terhadap Kinerja - Mitha Niviantari, Ni Putu Ayu; Putu Kawiana, I Gede (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
The purpose of this study was to determine how the influence of transformational leadership and empowerment on job satisfaction either partially or simultaneously. This research was conducted at the General and Protocol Bureau of the Bali Provincial Secretariat with the number of samples taken as many as 97 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. While the data analysis techniques are instrument test, classical assumption test, multiple linear regression analysis, multiple correlation, t test (t test), determination, and F test (F test). The test results show that there is a positive and significant effect between transformational leadership on job satisfaction as seen from the t-test results obtained t1-count is 5.616 which is greater than t-table of 1.671 and sig value of 0.000 so that the first hypothesis is accepted. There is a positive and significant effect between empowerment and job satisfaction as seen from the results of the t-test, it is obtained that t2-count is 3.746 which is greater than t-table of 1.671 and sig value of 0.000 so that the second hypothesis is accepted. There is a positive and significant effect between transformational leadership and empowerment on job satisfaction as seen from the F-count is 37.010 which is greater than the F-table of 3.15 so that the third hypothesis is accepted.